Emission in the Biological Window from AIE-Based Carbazole-Substituted Furan-Based Compounds for Organic Light-Emitting Diodes and Random Lasers - Lupinska, Kamila; Kotowicz, Sonia; Grabarz, Anna; Siwy, Mariola; Sulowska, Karolina; Mackowski, Sebastian; Bu, Lulu; Bretonnière, Yann; Andraud, Chantal; Schab-Balcerzak, Ewa; Sznitko, Lech (ACS omega, 2024)
The emission quenching observed in devices utilizing luminescent materials such as solid thin films is a prevalent issue. Consequently, searching for new organic luminescent compounds exhibiting aggregation-induced emission (AIE) behavior and characterized by relatively simple and cost-effective synthesis is of crucial interest among applications from optoelectronics and organic lasing branches. Herein, we report the optical properties of three furan-based carbazole-substituted compounds, namely, tBuCBzSO2Ph, tBuCBzSPh, and tBuCbzTCF, exhibiting the aforementioned AIE phenomenon. The optical properties of dyes were determined in classical spectroscopic experiments supported by quantum-chemical calculations. The thermal investigations and electrochemical properties of dyes were performed to verify their usefulness in the construction of organic light-emitting diodes (OLEDs). In pursuit of this objective, OLEDs with a different design were fabricated, and their performance was subject to evaluation. In more detail, the different design strategies relying on the utilization of neat-dye films, as well as the preparation of dye-doped poly(9-vinylcarbazole):2-(4-tert-butylphenyl)-5-(4-biphenylyl)-1,3,4-oxadiazole (PVK:PBD) matrices were examined. The analysis that was conducted indicated the superior potential of tBuCBzSPh for optoelectronic applications. Notably, the positive impact of the AIE effect on the emission of the OLEDs and the ability to establish the lasing phenomenon in asymmetric, poly(methyl methacrylate) (PMMA)-doped polymeric slab waveguides were verified. The study showed that the combination of the strong intramolecular charge transfer (ICT) effect with dye aggregation enables the tuning of the emission of the OLED toward the first biological window, making examined dyes promising candidates for biomedical purposes. The same optical region can be attained for laser emission at relatively low pumping conditions, reaching as low as 7.3 kW of optical power for the tBuCBzSO2Ph compound.